IMPLEMENTASI PROGRAM â€œMENJELAJAH DESA MENJEMPUT PAJAKâ€ PADA KANTOR BADAN PENDAPATAN KABUPATEN LANGKATâ€ - Putri, Dwi Nur Anisya; Badaruddin, Badaruddin; Kadir, Abdul (PERSPEKTIF, 2020)
This research aims to explain how the implementation of the village's Explore service program is picking up taxes related to UN-P2 services at the Langkat District Revenue Board. In addition, the research aims to determine what factors that can encourage and inhibit the implementation of the village-exploring program to pick up taxes on the district Revenue Board of Langkat. The form of research used in this study is descriptive research with a qualitative approach. This study used Edward III's theory. The informant used in this study was the head of the Langkat District Revenue board and the officers who conducted UN services-P2 as well as taxpayers in Langkat district. The data used in this research is primary data as well as secondary data as complementary data. Qualitative analysis in this study was conducted with an inductive logic approach. Based on the results of the research can be noted that the implementation of the program to explore the village picking up taxes in the District Revenue Board of Langkat is generally well-done. Contributing factors to the success of implementation of village-exploring program to collect tax in the Regional Revenue Board of Langkat District are: Commitment of leadership and resources. The Factor is a low community awareness inhibitor, and there are some cases where taxpayers do not want to pay the UN for reasons that they are not the owner of a tax object but only contracted or so on. Afandi, M. I., & Warjio, W. (2016). Implementasi Peraturan Daerah Kabupaten Asahan Nomor 11 Tahun 2011 Tentang Pajak Daerah Dalam Pencapaian Target Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan (Studi Deskriptif Di Kelurahan Bunut Barat Kecamatan Kota Kisaran Barat). Jurnal Administrasi Publik: Public Administration Journal, 5(2), 132-153.Anshori, A.G. (2009). Perbankan Syariah di Indonesia, Yogyakarta: Gadjah Mada University PressArikunto, S. (2006). Metode Penelitian Kualitatif. Jakarta: Bumi Aksara. Batinggi A, Badu Ahmad. (2013). Manajemen Pelayanan Publik. Yogyakarta: Penerbit Andi.Bungin, B. (2007). Penelitian Kualitatif: Komunikasi, Ekonomi, Kebijakan. Publik dan Ilmu Sosial lainnya. Jakarta: Putra Grafika Dunn, W.N. (1998). Muhadjir Darwin (Penyunting). Pengantar Analisis Kebijakan Publik. Yogyakarta: Gadjah Mada University PressHardjanto, A. (2008). Implementasi Kebijakan Pajak Bumi Dan Bangunan Di Kelurahan Gisikdrono Kecamatan Semarang Barat Kota Semarang (Doctoral dissertation, Diponegoro University, Faculty of Social and Political Science).Harefa, M. (2016). Kendala Implementasi dan Efektivitas Pemungutan Pajak PBB-P2 oleh Pemerintah Kota Makassar. Jurnal Ekonomi dan Kebijakan Publik, 7(1), 67-82.Ibrahim, A. (2008). Teori dan Konsep Pelayanan Publik Serta. Implementasinya. Jakarta: Mandar Maju.Kiwang, A. S., Pandie, D. B., & Gana, F. (2014). Analisis Kebijakan dan Efektivitas Organisasi. JKAP (Jurnal Kebijakan dan Administrasi Publik), 19(1), 71-82.Menteri Pendayagunaan Aparatur Negara RI. Keputusan Menteri Pendayagunaan Aparatur Negara Nomor: 63/KEP/M.PAN/7/2003. Tentang Pedoman Umum Penyelenggaraan Pelayanan PublikMoenir. A.S.  (2003). Manajemen Pelayanan Umum Di Indonesia. Jakarta: Aksara.Mulyadi, D, (2016), Administrasi Publik dan Pelayanan Publik, Bandung, Alfabeta.Nawawi, I. (2009). Public Policy, Analisis, Strategi Advokasi Teori dan Praktek. Surabaya: PMN.Nugroho, D,R. (2002). Kebijakan Publik untuk Negara-Negara Berkembang. Jakarta: PT Elex Media Komputindo.Nugroho, R. (2014). Public Policy. Jakarta: PT. Elex Media KomputindoParsons, W. (2014). Public Policy: Pengantar Teori dan Praktik Analisis Kebijakan. Jakarta: PT. Prenadamedia GroupPasolong, H. (2010). Teori Administrasi Publik, Alfabeta, Bandung.peraturan Bupati (Perbup) Nomor 66 tahun 2016 tentang rincian tugas dan Fungsi Badan Pendapatan Daerah Kabupaten LangkatRepublik Indonesia. Undang-Undang Republik Indonesia Nomor 25 Tahun 2009 tentang Pelayanan PublikSaputri, E., Hakim, A., & Noor, I. (2015). Implementasi Kebijakan Pemungutan Pbb?P2 di Kecamatan Galis Kabupaten Pamekasan. JISIP: Jurnal Ilmu Sosial Dan Ilmu Politik, 4(3).Sinambela, L.P. (2014). Metodologi Penelitian Kuantitatif. Yogyakarta: Graha IlmuSolichin, A.W. (2002). Analisis Kebijaksanaan, Dari Formulasi Ke Implementasi Kebijaksanaan Negara. Jakarta: Bumi Aksara.Sugiyono. (2012). Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta.Sugiyono. (2016). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: PT Alfabet.Suharto, E. (2005). Analisis Kebijakan Publik: Panduan Praktis Mengkaji Masalah dan Kebijakan Sosial. Bandung: AlfabetaSurjadi. (2009). Pengembangan Kinerja Pelayanan Publik. Bandung: PT. Reflika AditamaTahir, A. (2014). Kebijakan Publik dan Transparansi Penyelenggaraan Pemerintah Daerah. Alfabeta. Bandung.Thoha, M. (2008). Perilaku Organisasi, Konsep Dasar dan Aplikasinya. Jakarta: Raja Grafindo Persada.Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintah Daerah.Undang-Undang Nomor 28 Tahun 2009 Tentang Pajak Daerah dan Retribusi DaerahUndang-Undang Nomor 33 Tahun 2004 Tentang Perimbangan Keuangan Antara Pemerintah Pusat dan Pemerintah DaerahWinarno, B. (2016). Kebijakan publik era globalisasi (teori, proses dan studi kasus kompratif), Yogyakarta: CAPC (Center Of Academic Publishing ServiceWinarsih, S.A. & Ratminto. (2012). Manajemen Pelayanan. Yogyakarta: Pustaka Pelajar